Food items and foraging sites of the oriental pied-hornbill (Anthracoceros albirostris) during breeding season in Sungai Panjang, Sabak Bernam, Malaysia - Abdul Rahman, Mohd Faid; Ismail, Ahmad; Mohd Jamil, Nurul Huda (Universiti Putra Malaysia Press, 2019)
The Oriental pied-hornbill (Anthracoceros albirostris) is highly adaptable to habitat changes compared with other hornbill species. Although the species is omnivorous, their diet varies between seasons and can be restricted by food availability and abundance in the forest. Recently, Oriental pied-hornbills were spotted breeding at a human settlement in the rural area of Sungai Panjang, Selangor in abandoned clay jars. As the female seals itself in the nest, the male plays an important role in provisioning its partner and the chicks. Therefore, this study aimed at understanding the male's food items and foraging sites selection in Sungai Panjang during the breeding season. Three hornbill pairs were monitored between 2009 and 2011 to examine their foraging activities. Video recorders were used and the males were followed every alternate day to their respective foraging sites. Results showed the number of visits made and foods brought back by the males to the nests were dependent on the location of their nests. The average visits recorded were between four and 12 times a day (mean visit per day: 9.07 ± 3.40). In addition, they utilised different foraging areas, such as oil palm plantations, orchards and forest patches. Interestingly, 50% of animals were brought back to the nests after visits to plantations compared with fruits that were gathered mainly from the orchard (48%), while the rest (2%) was unidentified. Forest patches were the least utilised site. In sum, the species has taken advantage of Sungai Panjang's agricultural background particularly during its breeding season. The findings confirm the species high adaptability to disturbed habitat.